Pengukuran Kualitas Layanan untuk Meningkatkan Kepuasan dan Loyalitas Pelanggan di PT Mimosa Putra Abadi - Sase, Fitria Aprilindo; Merdiyanti, Angelia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
PT Mimosa Putra Abadi experienced a problem of low entry service units throughout 2021, only in February that exceeds the target. This problem is allegedly influenced by the service quality and customer satisfaction. This research aims to know the impact of service quality on customer satisfaction, customer satisfaction on customer loyalty, service quality on loyalty and the influence of service quality on customer loyalty through customer satisfaction. This research was conducted at PT Mimosa Putra Abadi with the research object user of service and is conducted for seven months from April to November 2022. Determination of sample size using non-probability sampling method and obtained calculation of sample counts are 100 respondents. Sample selection using purposive sampling method. Data collection using questionnaire instruments by responding to 1-6 likert scale statements. Instrument eligibility test using validity and reliability test. Data analysis uses path analysis methods that begin with descriptive analysis of respondents, further analysis of classical assumptions in the form of testing of normality and homogeneity. Hypothesis test is done using the test t which subsequently performs sobel test. The results of this study found that the quality of service impact on customer satisfaction has positive and significant influence, the impact of customer satisfaction on customer loyalty has positive and significant influence, the effect of quality service on customer loyalty has positive and significant influence. Based on Sobel testing it is found that the quality of service on service loyalty has a stronger value when through customer satisfaction. Keywords: Service Quality, Customer Satisfaction, Customer Loyalty